Spatial Price Competition and the Demand for Freight Transportation - Inaba, Fred S.; Wallace, Nancy E. (The Review of Economics and Statistics, 1989)
Two important issues in econometric freight transportation demand analysis are addressed: (1) the simultaneity between quantity shipped and mode/destination choices, and (2) the effect of spatial price competition on the demand for the transportation factor. In the theoretical model, spatial price competition determines the firm's market area and, thus, determines its sales and shipment sizes. The model is estimated using switching regression techniques, since shipment size and mode/destination choice are derived from the same optimization problem. The empirical model provides consistent estimates of unconditional freight demand. These estimates are needed to forecast transportation flows and derive elasticities for policy analysis. Copyright 1989 by MIT Press.